Telehealth: Passing Fad or Lasting Benefits? - Lehoux, P. (Can J Public Health, 2000)
Advocates of telehealth argue that the delivery of health services by means of communications technologies is both feasible and desirable. Nevertheless, the benefits of telehealth, due to the variety of its applications and their uneven development, are not self-evident. The goal of this paper is to reflect on the processes by which telehealth applications do or do not contribute to the delivery of health services. We propose a framework structuring a preliminary analysis of the match between needs and the possibilities offered by telehealth. Four mechanisms of expected benefits are discussed: 1) decreasing patient transfers; 2) decreasing trips by providers and patients; 3) meeting the needs of underserved populations; and 4) building providers’ and patients’ knowledge and reducing rural isolation. We conclude by stressing that the participation of providers is crucial, both in the research on telehealth and in the steering of its evolution.